Respiratory diseases and gut microbiota: relevance, pathogenesis, and treatment - Sun, Mengdi; Lu, Fang; Yu, Donghua; Wang, Yu; Chen, Pingping; Liu, Shumin (Frontiers in Microbiology, 2024)
Preclinical evidence has firmly established a bidirectional interaction between the lung, the gut, and the gut microbiome. There are many complex communication pathways between the lung and intestine, which affect each other's balance. Some metabolites produced by intestinal microorganisms, intestinal immune cells, and immune factors enter lung tissue through blood circulation and participate in lung immune function. Altered gut-lung-microbiome interactions have been identified in rodent models and humans of several lung diseases such as pulmonary fibrosis, chronic obstructive pulmonary disease, lung cancer, asthma, etc. Emerging evidence suggests that microbial therapies can prevent and treat respiratory diseases, but it is unclear whether this association is a simple correlation with the pathological mechanisms of the disease or the result of causation. In this review, we summarize the complex and critical link between the gut microbiota and the lung, as well as the influence and mechanism of the gut microbiota on respiratory diseases, and discuss the role of interventions such as prebiotics, and fecal bacteria transplantation on respiratory diseases. To provide reference for the rational design of large-scale clinical studies, the direct application of microbial therapy to respiratory related diseases can reduce the incidence and severity of diseases and accompanying complications.